Response of anaerobic granular sludge to long-term loading of roxarsone: From macro- to micro-scale perspective. (1st October 2021) - Tang, Rui; Luo, Haiping; Prommer, Henning; Yue, Zhengbo; Wang, Wei; Su, Kuizu; Hu, Zhen-Hu
Highlights: Roxarsone causes a substantial inhibition of methanogenic activity. Inhibition of methanogenic activity dissipates after an acclimatization period. The ability of anaerobic granular sludge (AGS) to resist As is gradually enhanced. Roxarsone stimulates EPS excretion and surface spalling of the AGS. The response of key functional microbes within the AGS to roxarsone is elucidated. Abstract: Extensive use of organoarsenic feed additives such as roxarsone has caused organoarsenicals to occur in livestock wastewater and further within anaerobic wastewater treatment systems. Currently, information on the long-term impacts of roxarsone on anaerobic granular sludge (AGS) activity and the underlying mechanisms is very limited. In this study, the response of AGS to long-term loading of roxarsone was investigated using a laboratory up-flow anaerobic sludge blanket reactor spiked with 5.0 mg L −1 of roxarsone. Under the effect of roxarsone, methane production decreased by ∼40% due to the complete inhibition on acetoclastic methanogenic activity on day 260, before being restored eventually. Over 30% of the influent arsenic was accumulated in the AGS and the capability of AGS to prevent intracellular As(III) accumulation increased with time. The AGS size was reduced by ∼30% to 1.20‒1.26 mm. Based on morphology and confocal laser scanning microscopy analysis, roxarsone exposure stimulated the excretion of extracellular polymeric substances and the surface spalling of AGS. High-throughput sequencing analysis further indicated roxarsone initially altered the acidogenic pathway and severely inhibited the acetoclastic methanogen Methanothrix . Acetogenic bacteria and Methanothrix were finally enriched and became the main contributor for a full restoration of the initial methane production. These findings provide a deeper understanding on the effect of organoarsenicals on AGS, which is highly beneficial for the effective anaerobic treatment of organoarsenic-bearing wastewater. Graphical abstract: Image, graphical abstract